Religion and Nationalism in Chinese Societies - Kuo, C.T (Amsterdam University Press, 2017)
Religion and Nationalism in Chinese Societies explores the interaction between religion and nationalism in the Chinese societies of mainland China, Taiwan and Hong Kong. On the one hand, state policies toward religions in these societies are deciphered and their implications for religious freedom and regional stability are evaluated. On the other hand, Chinese Buddhism, Tibetan Buddhism, Daoism, Christianity, Islam and folk religions are respectively analyzed in terms of their theological, organizational and political responses to the nationalist modernity projects of these states. What is new in this book on Religion and Nationalism in Chinese Societies is that the Chinese state has strengthened its control over religion to an unprecedented level. In particular, the Chinese state has almost completed its construction of a state religion called Chinese Patriotism. But at the same time, what is also new is the emergence of democratic civil religions in these Chinese societies.